Potential of Natural Fibers in Composites for Ballistic Applications – A Review. Issue 5 (4th May 2022) - Nayak, Suhas Yeshwant; Sultan, Mohamed Thariq Hameed; Shenoy, Satish B.; Kini, Chandrakant R.; Samant, Rashmi; Shah, Ain Umaira Md; Amuthakkannan, P.
ABSTRACT: In this paper, a review of natural fibers composites used in protective armors for ballistic applications like bulletproof vests is presented. It seeks to compile the results and establish natural fiber composites as an alternative to absolute synthetic composites used for the same application. The review assesses the latest articles under two categories viz. only natural fibers and hybrid composites with natural and synthetic fibers. It covers a range of fibers from flax, basalt, curaua, kenaf, aramid, jute, coir, and hemp. The study systematically classifies the composites based on the ballistic limit they exhibit and the back face signature measured during standardized ballistic testing. In accordance with the results, the findings are compared against standard materials such as Kevlar used in ballistic armors. The hybrid composites are seen to present superior properties in comparison to plain natural fiber composites. Natural fibers provide an ecological and economical alternative to existing composites. The review shows promising results and immense future scope for natural fibers in the area of ballistic applications and they must be actively considered for replacing synthetic fibers in armor.